2021
DOI: 10.1093/jhps/hnab060
|View full text |Cite|
|
Sign up to set email alerts
|

Short-term outcomes following mini-open repair of chronic gluteus medius tendon tears using a double-row technique

Abstract: Gluteal tendon tears represent a common but underreported cause of lateral hip pain and dysfunction. In case of conservative management failure, a surgical procedure must be performed to relieve patient symptoms. Current operative treatments, either open or endoscopic, have been however associated with different drawbacks which led to the introduction of the mini-open technique. The aim of this study was to evaluate and report the short-term outcomes of patients operated through the aforementioned surgical tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Each have various indications and are optimal in different clinical situations. 1,[3][4][5][6][8][9][10] Considerations for augmentation with acellular allograft are based on the size of the tear, tissue quality, and tendon excursion. While the gluteus Medius is a big muscle, it has a short tendon, so in cases with questionable tendon quality or likely tension on the repair, a patch can provide structural integrity to pass sutures through.…”
Section: Video Transcriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Each have various indications and are optimal in different clinical situations. 1,[3][4][5][6][8][9][10] Considerations for augmentation with acellular allograft are based on the size of the tear, tissue quality, and tendon excursion. While the gluteus Medius is a big muscle, it has a short tendon, so in cases with questionable tendon quality or likely tension on the repair, a patch can provide structural integrity to pass sutures through.…”
Section: Video Transcriptmentioning
confidence: 99%
“…2 Another recent study using a mini-open double-row technique found patients had significantly improved abductor strength, decreased Trendelenburg sign, and improved mHHS scores, providing clinical evidence of technique efficacy. 1…”
Section: Video Transcriptmentioning
confidence: 99%
“…Since 1998, when Kagan et al first described gluteal tendon repair, several techniques have been published and reviewed in the literature [47][48][49][50][51][52][53][54] . Primary open and endoscopic techniques have shown good clinical outcomes for patients suffering from abductor tendon tears [47][48][49] (Fig.…”
Section: Operative Techniquesmentioning
confidence: 99%
“…With suture anchor fixation, the construct may be either single-row (SR) or double-row (DR) 53,54 . In a cadaveric biomechanical study from 2019, Kahlenberg et al found that DR repairs for gluteal tendon tears improved the footprint coverage compared with SR repairs, and there was a higher mean yield load in DR repairs, although not significant (p = 0.15) 56 .…”
Section: Operative Techniquesmentioning
confidence: 99%
“…Greater trochanteric pain syndrome (GTPS) affects up to 25% of the general population [ 25 , 37 ]. While the exact incidence of hip abductor tendon tears in those presenting with symptomatic GTPS has not been reported to the best of our knowledge, their contribution is now acknowledged more widely and highlighted by the array of open, endoscopic and augmented surgical techniques now reported [ 2 , 7 , 11 , 13 , 15 , 16 , 18 , 22 , 23 ]. Published reviews have reported encouraging outcomes overall [ 1 , 4 , 8 , 19 21 , 26 , 39 ], with patient satisfaction rates ranging from 66 to 90%, [ 3 , 31 , 32 , 36 ] and similar clinical and functional outcomes in patients undergoing open and endoscopic hip abductor tendon repair methods [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%